2015
DOI: 10.1146/annurev-soc-073014-112340
|View full text |Cite
|
Sign up to set email alerts
|

Sociology and School Choice: What We Know After Two Decades of Charter Schools

Abstract: Charter schools have been on the educational reform landscape for over twenty years. In the last ten years, a number of rigorous studies have examined the effects of these schools on student achievement and educational attainment. Findings reveal mixed results where student achievement is concerned (i.e., some positive, some negative, some neutral) and positive results in terms of educational attainment (i.e., high school graduation and college attendance). The article places this research within a framework t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(139 citation statements)
references
References 66 publications
(50 reference statements)
2
128
0
5
Order By: Relevance
“…The effects of charter schools on academic achievement are vigorously debated, though most analyses suggest that many students' scores do not increase after moving to charter schools (e.g., Bettinger, 2005;Bifulco & Ladd, 2007;Chingos & West, 2015;Clark, Gleason, Tuttle, & Silverberg, 2015), that charter schools may have mixed or negative effects on a TPS (Bettinger, 2005;Zimmer et al, 2009), and there may be high student attrition from charters (Miron, Urschel, & Saxton, 2011). Moreover, most researchers agree that there is considerable variety in student outcomes within the charter school sector (Berends, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of charter schools on academic achievement are vigorously debated, though most analyses suggest that many students' scores do not increase after moving to charter schools (e.g., Bettinger, 2005;Bifulco & Ladd, 2007;Chingos & West, 2015;Clark, Gleason, Tuttle, & Silverberg, 2015), that charter schools may have mixed or negative effects on a TPS (Bettinger, 2005;Zimmer et al, 2009), and there may be high student attrition from charters (Miron, Urschel, & Saxton, 2011). Moreover, most researchers agree that there is considerable variety in student outcomes within the charter school sector (Berends, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…Like others (Berends, 2015), we read this literature as suggesting that school markets do not uniformly trigger the effects proposed by choice advocates, such as increased differentiation and technical orientations, but do so only under certain conditions. In light of such findings, we seek to inquire: Why are market effects seemingly contingent, and under which conditions are they strong or weak?…”
Section: Rationale For This Studymentioning
confidence: 87%
“…Such tests have become feasible in recent years as choice initiatives have gained traction throughout the United States, and have even perforated some Canadian provinces (Bossetti & Gereluk, 2016). Numerous scholars have become interested in different kinds of private schools and other schools of choice, creating a specialist literature on educational markets (see Berends, 2015;Davies & Quirke, 2007;Lubienski, 2003;Lubienski & Lee, 2016). Such work has found that competition does not uniformly shape school structures and practices, but does so only under specific conditions.…”
mentioning
confidence: 99%
“…Racial equity in education has often been pursued through multiple avenues, including legal remedies such as desegregation and affirmative action (Orfield, 2014), the enactment of national educational standards and accountability policies (Darling-Hammond, 2010), and market-based reforms (Berends, 2015). But these efforts have not significantly disrupted P-16 racial inequities (Carnevale & Strohl, 2013;Ladson-Billings, 2006), in part, we argue, because they fail to address the dynamic and structurally embedded nature of racism in our country.…”
Section: Westedmentioning
confidence: 97%